Advances in Aquaculture Ecology Research - Tian, Xiangli; Li, Li (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The discipline of aquaculture ecology is developing rapidly and has generated much valuable progress in recent decades. This reprint mainly describes the recent advances in the individual ecology of commercial aquatic organisms, the ecology of aquaculture systems, the interaction between aquaculture activities and the environment, the structure of function of microbial communities, the principles of environmental management in aquaculture ecosystems, etc. Aquaculture is one of the fastest-growing human activities, and has achieved high and predictable yields in recent decades. However, the industry is also facing numerous long-term challenges, such as environmental pollution, excessive resource consumption, etc. Aquaculture ecology aims to lay an ecological foundation for the sustainable development of aquaculture. This reprint hosts 10 papers and 1 editorial, with topics including, but not limited to, the impact of floating raft aquaculture on the hydrodynamic environment of an open sea area; the bioremediation of aquaculture wastewater using seaweed; the production environment in biofloc systems; the effects of various environmental factors, including temperature, carbonate alkalinity and protein levels in compound feed on commercial aquatic species; advances in ecology research on major integrated rice field aquaculture models in China, etc. The advances in aquaculture ecology research collected in this reprint can provide references for the sustainable development of aquaculture.